PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS CONTEXTUAL TEACHING AND LEARNING DENGAN APLIKASI POWTOON PADA MATERI BANGUN RUANG SISI LENGKUNG KELAS IX SMP - Nisa Vebriani (Departemen Matematika, 2021)
The aims this research is to develop learning media in the form of animated videos with a contextual approach to valid and practical curved side space material. The type of this research.is development.research.by.the Plomp rnodel which is grouped in the prelirnrinary research phase, prototyping phase, and assessrnent stage. Preliminary research stage includes analysis of needs, analysis of student, analysis of curriculum, and analysis of material. Prototyping phase is the stage for developing CTL-based learning videos with the application of powtoon on curved side-space materials. The prototype must go through evaluation with several stage in the form of self-evaluation and”expert”reviews to obtain a valid prototype. Results demonstrate that the CTL-based learning video with the application of powtoon on curved side space’’has a validity’’ level of 86.11% with.a.very.valid category and.the.practicality level with a very practical category is 87.15% by students and 94.37% by educators. Keywords– Contextual Teaching and Learning (CTL), video powtoon application, video teaching learning.